Extreme Weather Conditions and Cardiovascular Hospitalizations in Southern Brazil - Iago Turba Costa (MDPI AG, 2021)
This research concerns the identification of a pattern between the occurrence of extreme weather conditions, such as cold waves and heat waves, and hospitalization for cardiovascular diseases (CVDs), in the University Hospital of Santa Maria (HUSM) in southern Brazil between 2012 and 2017. The research employed the field experiment method to measure the biometeorological parameters associated with hospital admissions in different seasons, such as during extreme weather conditions such as a cold wave (CW) or a heat wave (HW), using five thermal comfort indices: physiologically equivalent temperature (PET), new standard effective temperature (SET), predicted mean vote (PMV), effective temperatures (ET), and effective temperature with wind (ETW). The hospitalizations were recorded as 0.775 and 0.726 admissions per day for the winter and entire study periods, respectively. The records for extreme events showed higher admission rates than those on average days. The results also suggest that emergency hospitalizations for heart diseases during extreme weather events occurred predominantly on days with thermal discomfort. Furthermore, there was a particularly high risk of hospitalization for up to seven days after the end of the CW. Further analyses showed that cardiovascular hospitalizations were higher in winter than in summer, suggesting that CWs are more life threatening in wintertime.